Toward a Set of Criteria to Decide Which STIs to Screen for in PrEP Cohorts - Kenyon, Chris (Frontiers in Public Health, 2019)
Contemporary HIV preexposure prophylaxis (PrEP) cohorts are characterized by high rates of partner change and as a result have high and fairly stable prevalences of N. gonorrhoeae and C. trachomatis. The available evidence suggests that intensive 3-monthly screening in this setting does not have a large effect on the prevalence of these infections but results in high antimicrobial exposures. Gonorrhoea/chlamydia screening may thus be doing more harm than good. Compelling arguments can, however, be made to screen for HIV, hepaptitis C and syphilis in PrEP cohorts. In this perspective piece, we explore the logical basis for deciding which STIs to screen for in PrEP cohorts. We propose that a Delphi consensus methodology is used to derive, assess and apply a broadly accepted set of criteria to evaluate which STIs to screen for in these cohorts. Finally, to illustrate the utility of the process, we derive and apply our own list of criteria as to which STIs to screen for. This process leads to a controversial conclusion, namely that stopping gonorrhoea/chlamydia screening in a controlled and phased manner may offer net health benefits to PrEP cohorts.